1976
DOI: 10.1139/m76-136
|View full text |Cite
|
Sign up to set email alerts
|

Colonial variation in Xanthomonas campestris NRRL B-1459 and characterization of the polysaccharide from a variant strain

Abstract: Stock cultures of Xanthomonas campestris NRRL B-1459 require special attention to maintenance and propagation to assure consistent production in good yields of the extracellular polysaccharide xanthan. Under customary conditions of propagative maintenance on agar slants, variant colony types develop that are smaller in size than the normal type. The rate of regression of the normal to the variant forms was diminished when the D-glucose content of the stock medium was sufficient to avoid depletion during storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
4

Year Published

1978
1978
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(59 citation statements)
references
References 12 publications
2
53
0
4
Order By: Relevance
“…Xcc strains 8004 (wild type), 8397 (gum::Tn5lac; EPS minus), and 8396 (gum::Tn5lac; truncated EPS ) were described previously (Cadmus et al, 1976;Daniels et al, 1984;Tang et al, 1991;Slater et al, 2000) and characterized (Vojnov et al, , 2002. Xcc strains were cultured in a 28°C shaker in PYM medium as reported by Cadmus and collaborators (1976).…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xcc strains 8004 (wild type), 8397 (gum::Tn5lac; EPS minus), and 8396 (gum::Tn5lac; truncated EPS ) were described previously (Cadmus et al, 1976;Daniels et al, 1984;Tang et al, 1991;Slater et al, 2000) and characterized (Vojnov et al, , 2002. Xcc strains were cultured in a 28°C shaker in PYM medium as reported by Cadmus and collaborators (1976).…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
“…Bacterial suspensions (OD 600 5 0.05) were prepared from 24 h/28°C PYM-liquid Xcc cultures (Cadmus et al, 1976) with 10 mM MgCl 2 , and Silwet L-77 was added (200 mL/L). Plant pots (nine seedlings each) were submerged upside down in the bacterial solution for 30 s and then covered with a transparent lid.…”
Section: Arabidopsis Inoculationsmentioning
confidence: 99%
“…About one-half or one-third of the terminal mannose residues bear a pyruvic acid, depending on the culture conditions. 7 ) The acetyl residues of xanthan have been suggested to contribute to its intramolecular association,S) though this has not been discussed with regard to its rheological properties. Deacetylation can be done without further modification of the polymeric structure by mild alkaline treatment.…”
mentioning
confidence: 99%
“…A problem arising in screening microorganisms for polysaccharide production is the lack of suitable techniques for selection of potential strains. Cadmus et al (1) reported that some morphological characteristics of colonies of Xanthomonas could be correlated with polymer production and pyruvic acid content. Kidby et al (4) found that small colony variants produce gums of lower quality whereas large colonies produce higher quality gums; virulence and infrared spectra of polymers and penicillin G sensitivity were also suggested (7,12).…”
Section: Resultsmentioning
confidence: 99%